Evaluation of the implementation of language policy in lower primary education in selected schools in Ibadan, Oyo state, Nigeria (2016)
This study examines and evaluates the implementation of the pronouncement of the Nigerian government on the use of mother tongue (Yoruba to be specific) in lower primary schools. The study employ is a descriptive research method. The study population was primary 1-3 teachers in public primary schools in Ibadan North Local Government Area of Oyo State. Simple random sampling technique was used to select twelve (12) public primary schools with questionnaire given to 3 teachers in each arm of the schools. The questionnaire was styled, “Teacher Questionnaire on Implementation of Language Policy” (T.Q.I.L.P). Research questions were analysed in accordance with the sequential arrangement of questions in the questionnaire with the drawn table featuring the statistical data while analysis of the same data is given thereafter in form of an exposition. On the basis of findings, it was realized that the policy on the use of mother tongue (Yoruba) exists on paper and it is not taken seriously by educational practitioners. For effective implementation, this study recommended that: the government and the policy makers should fully revise the language policy component with a view of correcting the inherent loopholes in it; the production of textbooks, readers, and other literary materials should be attended to by the stakeholders in education industry; the training of teachers in the use of the mother tongue (Yoruba) should be given priority by the government; each Local Government Authority should saddle its supervisory unit with the responsibility of ensuring adequate monitoring of the implementation of the language policy at the basic levels